2018
DOI: 10.1111/joop.12199
|View full text |Cite
|
Sign up to set email alerts
|

The affective relevance of suggestion‐focused and problem‐focused voice: A diary study on voice in meetings

Abstract: Building on the affective events theory framework, we argue for voice as affect‐relevant action and investigate the affective consequences of voice in meetings within persons. We administered daily surveys over one workweek to examine how suggestion‐focused and problem‐focused voice in meetings relate to state positive and state negative affect at work. Our analyses are based on the data of 124 employees reporting on 224 meetings. Employees’ problem‐focused voice in meetings was associated with a decrease in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 85 publications
(125 reference statements)
0
34
0
Order By: Relevance
“…We focused on young participants early in their careers who had a college or university background, because research showed that these people are more likely to engage in sustainable entrepreneurship (Bosma et al, ). We used a mixed recruitment approach to obtain data from a convenience sample (Starzyk, Sonnentag, & Albrecht, ). We used an information sheet that described the purpose of the study and contained an online link to the study.…”
Section: Field Study: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on young participants early in their careers who had a college or university background, because research showed that these people are more likely to engage in sustainable entrepreneurship (Bosma et al, ). We used a mixed recruitment approach to obtain data from a convenience sample (Starzyk, Sonnentag, & Albrecht, ). We used an information sheet that described the purpose of the study and contained an online link to the study.…”
Section: Field Study: Methodsmentioning
confidence: 99%
“…Moreover, the mixed recruitment approach results in a more heterogeneous sample, increasing the generalizability of findings. It is important to note that the mixed recruitment approach does not usually bias study findings (Starzyk et al, ). In our sample, the average age was 25 years and 45% were female.…”
Section: Field Study: Methodsmentioning
confidence: 99%
“…By targeting communication patterns within meetings, several studies have linked behavioral patterns to outcomes of interest. For example, people who participate in a meeting by bringing up problems relating to poor work processes or performance feel less negative about their work a day after the meeting (Starzyk, Sonnentag, & Albrecht, 2018). On the other hand, when one person starts to complain in a meeting by expressing so-called “killer phrases” that reflect futility or an unchangeable state (e.g., “nothing can be done about that issue” or “nothing works”), other meeting attendees begin to complain, which starts a complaining cycle that can reduce group outcomes (Kauffeld & Lehmann-Willenbrock, 2012).…”
Section: Applying Meeting Science To Ensure Good Meetings: Key Questimentioning
confidence: 99%
“…First, the mediation of felt guilt in the relationship between UPB and promotive voice was not supported in our experiment due to the relatively low correlation between felt guilt and promotive voice. This may not be surprising because at an acute level, research show that prohibitive voice helps to decrease state negative emotions (such as guilty in this study) while promotive voice does not (Starzyk et al 2018). However, moral cleansing process is not limited in a short time (Cryder et al 2012) and we still need more evidence to detect this relationship.…”
Section: Study 1a Discussionmentioning
confidence: 67%